Selective Formation of Hägg Iron Carbide with g‐C3N4 as a Sacrificial Support for Highly Active Fischer–Tropsch Synthesis. Issue 21 (22nd October 2015) - Park, Hunmin; Youn, Duck Hyun; Kim, Jae Young; Kim, Won Yong; Choi, Yo Han; Lee, Young Hye; Choi, Sun Hee; Lee, Jae Sung
Abstract: The Fischer–Tropsch synthesis (FTS) is a feasible pathway to chemicals and fuels from underutilized resources like coal, natural gas, biomass, and shale gas, instead of the current petroleum‐based production. Owing to its high activity and low price, the iron‐based catalysts are widely used in FTS, yet catalysts with higher activity and better selectivity should be developed for widespread applications. Herein, we report a unique strategy to synthesize an efficient iron catalyst for FTS by applying a graphitic carbon nitride (g‐C3 N4 ) as a sacrificial support. The iron catalyst on g‐C3 N4 is effectively reduced to a state that is rapidly and selectively converted to highly crystalline and pure Hägg carbide (χ‐Fe5 C2 ) phase during the FTS reaction. The obtained catalyst exhibits outstanding CO conversion, and high selectivity for C5+ products, outperforming most of the recently reported carbon‐based iron catalysts. Abstract : Get ready for catalysis : The iron catalyst on g‐C3 N4 is effectively reduced to a state that is rapidly and selectively converted to highly crystalline and pure Hägg carbide (χ‐Fe5 C2 ) phase during Fischer–Tropsch synthesis reaction. The obtained catalyst exhibits outstanding CO conversion, and high selectivity for C5+ products, outperforming most of the recently reported carbon‐based iron catalysts.